Perbandingan Consideration of Future Consequences dalam Pengambilan Keputusan Vaksinasi pada Orang Tua - Ferida, Reni; Sulistyani, Arum; Kumala, Intan Dewi; Amna, Zaujatul (Universitas Airlangga, 2025)
Consideration of Future Consequences (CFC) refers to the extent to which individuals reflect on how their current behavior may affect future outcomes. This study aimed to examine the differences in CFC among parents in making vaccination decisions for their children. The study involved 120 parents, divided into two groups: parents who chose to vaccinate their children and parents who refused vaccination. The sampling technique used was non-probability sampling with an unrestricted self-selected survey, employing the Consideration of Future Consequences Scale (CFC-14) developed by Joireman. Data analysis using an independent sample t-test showed that parents who allowed their children to be vaccinated had significantly higher CFC scores compared to those who refused (p < 0.001). Therefore, educational efforts to promote child vaccination could incorporate information regarding the positive long-term impacts of vaccination.